Sistem Irigasi Cerdas Berbasis IOT Pada Tanaman Tomat dan Cabe di Kampung Sota Kabupaten Merauke - Xaverius, Fransiskus; Zubaedah, Reza; Djaja, Irba; Barumak, Agustinus (Abdimas Mandalika, 2026)
Abstract:  This community service project aims to implement an Internet of Things (IoT)-based smart irrigation system for tomato and chili plants in Sota Village, Sota District, Merauke Regency. The system is designed to help farmers automatically regulate irrigation based on soil moisture levels, optimizing water use and improving plant growth. The method involved designing both hardware and software components, field installation, and user training for local farmers. The system utilized NodeMCU (ESP8266), soil moisture sensors, solenoid valves, solar panels, and LiPo 3.7V batteries as independent power sources. The irrigation process is automatically activated when soil moisture drops below the threshold and can be monitored via a web-based dashboard. The results indicate a significant improvement in plant growth. Tomato plants reached 42 cm in height with the system compared to 24 cm without it, while chili plants grew 38 cm compared to 22 cm without the system. The lighter green leaves and thicker stems reflect healthier plant conditions. This IoT-based irrigation system is proven to be effective, energy-efficient, and suitable for wider implementation in remote agricultural areas.Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk menerapkan sistem irigasi cerdas berbasis Internet of Things (IoT) pada tanaman tomat dan cabai di Kampung Sota, Distrik Sota, Kabupaten Merauke. Sistem ini dirancang untuk membantu petani mengatur penyiraman tanaman secara otomatis berdasarkan tingkat kelembapan tanah agar penggunaan air lebih efisien dan pertumbuhan tanaman lebih optimal. Metode yang digunakan meliputi perancangan perangkat keras dan perangkat lunak sistem irigasi, instalasi di lahan uji, serta pelatihan penggunaan kepada mitra petani. Perangkat yang digunakan terdiri dari NodeMCU (ESP8266), sensor kelembapan tanah, solenoid valve, panel surya, dan baterai LiPo 3.7V sebagai sumber energi mandiri. Sistem mengatur penyiraman otomatis saat kelembapan tanah di bawah ambang batas yang ditentukan dan menampilkan data melalui dashboard web. Hasil pengujian menunjukkan peningkatan signifikan terhadap pertumbuhan tanaman. Tanaman tomat dengan alat tumbuh hingga 42 cm dibandingkan 24 cm tanpa alat, sedangkan tanaman cabai mencapai 38 cm dibandingkan 22 cm tanpa alat. Warna daun lebih hijau muda dan ukuran batang lebih besar menandakan kondisi tanaman yang lebih sehat. Sistem ini terbukti efektif, hemat energi, dan potensial untuk diterapkan secara luas di wilayah pertanian terpencil.